From global to local: examining the localization strategies of transnational format reality TV The Voice of China - XiaomengZhang, Zhang; Mohd Hasan, Nurul Ain; Yaakup, Hani Salwah; Ng, Chwee Fang (Human Resource Management Academic Research Society, 2023)
This study explores the localization of format television programs in China, specifically focusing on the renowned show The Voice of China. Through textual analysis of the 15 episodes of the tenth season of the program, the research examines how this popular singing competition serves as a platform for talent exhibition and a powerful tool for reconstructing media discourse power by integrating positive national image and ethnic culture. It reveals the interplay between media, culture, and national image in contemporary China. The findings show that it is a unique cultural hybridization, blending foreign modernity with local elements to present a novel form of local modernity. This research provides insights into the role of format television programs in shaping national identity and cultural representation, highlighting how the program promotes Chinese culture and fosters a sense of national pride among audiences.